Gambaran Religiusitas Pada Remaja Yang Kecanduan Minuman Keras (Alkohol) di Desa “X” - Kusuma, Dinar Sulistyaning; Hasanah, Muhimmatul; Wicaksono, Awang Setiawan (Universitas Maritim AMNI Semarang, 2024)
The highest level of alcohol consumption in education is among students. One of the factors causing the increase in alcohol consumption behavior and the rise in crime cases due to alcohol consumption is a lack of religiosity. Religiosity as the internalization of religious values related to belief in religious teachings. These beliefs are then actualized in human behavior. This research is included in the type of qualitative research with a case study approach. The conceptual boundaries of this research are religiosity, teenagers aged 18 - 21 years, and subjects who live in Village